Peningkatan Hasil Belajar IPA Dengan Penerapan Model Bertukar Pasangan Pada Siswa Sekolah Dasar - Rahmiwati Rahmiwati; Rizki Amalia (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research is motivated by the low learning result of science at the four year students of state elementary school 020 Pangkalan Baru District of Siak Hulu Regency of Kampar. One of solution to overcome this problem by implementation of exchange partners models. The objective of study to know increase learning result of science material part of the plant by implementation of exchange partners models at the four year students of state elementary school school 020 Pangkalan Baru District of Siak Hulu Regency of Kampar. This research is a kind of Classroom Action Research (CAR) executed in two cycles. Every cycles consisted of bay one meeting and four phase, thas is planning, action, observation, and reflection. Research time executed to August s/d September 2017. For the subjects in this study is the fourth grade students of 020 Pangkalan Baru District of Siak Hulu Regency of Kampar 2017-2018 school year the number of students of 20 people, consisting of 9 men and 11 women. Data collection techniques used in this study is the observation, testing, and documentation. Having conducted research note an increase in student learning outcomes of prior actions, the first cycle and second cycle. In the pre-action mastery students only reached 45,83% or 11 students who completed, the students who pass the first cycle increased to 14 people or completeness only reached 70,00%. In the second cycle turns completeness students at 19 students or the percentage of 95,00%. Thereby that is the implementation of exchange partners models to increase learning result of science material part of the plant at the four year students of state elementary school 020 Pangkalan Baru District of Siak Hulu Regency of Kampar.